The management of postoperative upper alimentary tract fistulas: A single-center experience of endoscopic tissue glue repair and recommendations of a systematic review - Peng-Sheng Lai; Chien-Te Pan; Po-Chu Lee; I-Rue Lai; Chiung-Nien Chen; Pei-Ming Huang; Ming-Tsan Lin (Journal of the Formosan Medical Association, 2022)
Background/purpose: The appropriate management of postoperative upper alimentary tract fistula (UATF) remains uncertain. The efficacy of esophagogastroduodenoscopy (EGD) tissue glue repair in the treatment of patients with postoperative UATF was explored. We also conducted a systematic review of the literature regarding the inpatient management of UATF. Methods: Totally 24 patients received EGD tissue glue repair for postoperative UATF at our institute from April 2014 to April 2020. Independent characteristics of size of fistula, location of the UATF, complications, and recurrences were analyzed. PubMed and Cochrane Library databases were reviewed. A pooled analysis was performed, and subgroup analysis was conducted separately for different anatomic locations and techniques. Results: With a mean follow-up of 40 months, the fistula failed to close with EGD tissue glue repair in 2 of 24 patients (8.3%). Eight patients required repeated EGD tissue glue repair, which was more frequent in oral or thoracic UATF (p = 0.053), but all achieved a successful seal in the EGD tissue after glue repair alone (n = 22). The fistula size was correlated with the demand for repeated EGD tissue glue repair (p = 0.017). Besides, a total of 30 studies regarding 2356 cases of postoperative UATF between 2010 and 2021 were retrieved and analyzed. Several non-operative methods were generally accepted as the initial approach, with a non-inferior success rate compared to operative techniques. Conclusion: The results suggest that no single approach toward UATF is superior in terms of success rate and healing time. The potential advantages of EGD tissue glue repair after drainage were more suitable for patients with postoperative UATF and multiple comorbidities.